Mecanismos celulares envolvidos na ação antiproliferativa do [10]-gingerol sobre células de tumor de mama - Fuzer, Angelina Maria (2016)
Cancer is a leading cause of death, according to World Health Organization, preceding diseases as diabetes and tuberculosis, conditions as malnutrition and even though interpersonal violence. Many types of cancer are also correlated to major risk factors associated to mortality and morbidity, such as obesity, alcohol abuse and smoking. In 2012 14.1 millions of new cases of cancer arisen with 8.2 million of deaths worldwide. Ginger rhizome (Zingiber officinale Roscoe) is word know use as spice on cooking and widely use as medicinal herb in preparations. Several studies describe its anti-inflammatory, antimicrobial, antioxidant and anti-emetic activities. Much of the ginger bioactivity is due to its phenolic compounds [6], [8], and [10]- gingerol, which have anti-proliferative and antiangiogenic action on tumor cells, as demonstrated by several in vivo and in vitro studies. Several studies have revealed advantages of three-dimensional culture techniques (3D) over traditional two-dimensional monolayer cultures (2D). 3D cultures better mimic the tumor microenvironment found in vivo, as well as the interaction of cells with the extracellular matrix (ECM). Three-dimensional culture has produced different responses compared to those found in 2D cultures, such as increased resistance of tumor cells to various drugs, and increased selective sensitivity to tumor cells in relation to normal cells. On this work, techniques for three-dimensional culture were used to test the effects of [10]-gingerol on breast tumor cells. The aim of this study was to evaluate the effects of [10]-gingerol in different hallmarks of malignancy correlated with metastatic process, such as adhesion, proliferation, migration, invasion and also its effects on apoptosis, both in 2D and 3D. Results demonstrated that [10]-gingerol changes the morphology of MDA-MB-231 malignant cells in lower concentrations and shorter times when compared to nonmalignant MCF-10A cells, suggesting an specific and concentration-dependent action for [10]-gingerol on malignant cells. [10]-gingerol was also able to inhibit migration and invasion of MDA-MB- 231 cells at low concentrations and to induce apoptosis at higher concentrations. We observed that [10]-gingerol presented higher IC50 in proliferation assays with MCF-10A non tumor cells compared to tumor cells. The compound also inhibited migration of non-tumor cell lines at higher concentrations compared to tumor cells. Moreover, [10]-gingerol inhibited MDA-MB- 231 cell adhesion to different ECM components, such as laminin, fibronectin and vitronectin, even at low concentrations. Western blotting and real time quantitative PCR assays suggested that [10]-gingerol was able to act by the intrinsic pathway of apoptosis, increasing Bax/Bcl-2 ratio and caspase-9 and caspase-3 mRNA and protein levels in MDA-MB-231 cells. On 3D assays the results showed selectivity of [10]-gingerol against the malignant T4-2 lineage. The compound was also able to revert the malignant phenotype and to induce apoptosis in this cell line. These results suggest that [10]-gingerol has potential to be a new anticancer drug in the future.